1998
DOI: 10.1002/(sici)1521-186x(1998)19:1<57::aid-bem7>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of prolonged exposure to ELF electromagnetic fields in rats: III. 50 Hz electromagnetic fields

Abstract: Groups of adult male Sprague Dawley rats (64 rats each) were exposed for 8 months to electromagnetic fields (EMF) of two different field strength combinations: 5mT -1kV/m and 100mT -5kV/m. A third group was sham exposed. Field exposure was 8 hrs/day for 5 days/week. Blood samples were collected for hematology determinations before the onset of exposure and at 12 week intervals. At sacrifice, liver, heart, mesenteric lymph nodes, bone marrow, and testes were collected for morphology and histology assessments, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 40 publications
3
31
0
Order By: Relevance
“…Jeong et al [2000] used a 60 Hz magnetic field at up to 2 mT for 24 h and found a circadian rhythm-dependent effect on pain in mice, with increased nociception at night for fields as low as 500 mT, but only at 2 mT during the day. A long-term study with rats exposed to 50 Hz fields at 5 and 100 mT for 8 h/day, 5 days/week, for 8 months found changes in the expression of opioid receptors in the brain, with differing changes in different regions, for example, an increase in m-opioid receptors in the hippocampus, and a decrease in the frontal cortex at 5 mT [Zecca et al, 1998]. …”
Section: Mechanisms: Opioidsmentioning
confidence: 99%
“…Jeong et al [2000] used a 60 Hz magnetic field at up to 2 mT for 24 h and found a circadian rhythm-dependent effect on pain in mice, with increased nociception at night for fields as low as 500 mT, but only at 2 mT during the day. A long-term study with rats exposed to 50 Hz fields at 5 and 100 mT for 8 h/day, 5 days/week, for 8 months found changes in the expression of opioid receptors in the brain, with differing changes in different regions, for example, an increase in m-opioid receptors in the hippocampus, and a decrease in the frontal cortex at 5 mT [Zecca et al, 1998]. …”
Section: Mechanisms: Opioidsmentioning
confidence: 99%
“…Numerous investigations, from monitoring changes at molecular levels to the behavioral aspects, have been carried out in vitro and in vivo in order to illustrate different effects of ELF/EMF e.g., its impacts on cells, 1 hormones, [2][3][4][5][6] neurophysiological properties and sleep, 7,8 biochemical factors and metabolism, 9-11 pathology, 12,13 DNA damages and chromosome abnormalities, [14][15][16][17][18][19] reproduction and development, 20 and cancer. [21][22][23] On the other hand, the fact that central nervous system (CNS) as a very complicated electrochemical system may be influenced by electromagnetic fields attracts many researches interests.…”
Section: Introductionmentioning
confidence: 98%
“…29 It has been shown that the cholinergic activity in the frontal cortex and hippocampus of the rat decreases immediately after exposure to 60 Hz magnetic field with different intensities 30 and 50 Hz ELF-EMF exposure can increase in vivo neurogenesis. 31 Zecca et al 12 reported that prolonged exposure to ELF/EMF increases the level of µ-opioid receptors in the rat brain. Some researchers reported that ELF-EMF altered the anxiety-like behavior in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental and biological studies have dealt especially with increased incidence of various types of cancer, including childhood leukemia, lymphomas, brain tumours and breast cancers, effects on reproduction and development and behavioral changes. 1,11 In vivo and in vitro investigations claim that extremely low-frequency magnetic field produced a genotoxic effect, originating from types of free radicals. 12,13 For biological effects of free radicals, especially reactive oxygen species (ROS) may produce cellular and toxic effects such as lipid peroxidation in cell membrane, protein degradation, enzyme inactivation.…”
Section: Introductionmentioning
confidence: 78%
“…An increased health risk due to exposure to electromagnetic fields (EMF) at 50 and 60 Hz has been reported by several authors. [1][2][3][4] Iron is an essential element in a variety of vital processes, including respiratory electron transfer, oxygen transport. 5 However, when iron reacts with H 2 O 2 , hydroxyl radicals are produced via a Fentontype reaction.…”
Section: Introductionmentioning
confidence: 99%